2018
DOI: 10.1186/s13098-018-0368-8
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of educational intervention based on psychological factors on achieving health outcomes in patients with type 2 diabetes

Abstract: BackgroundManaging type 2 diabetes (T2D) is assumed to be heavily dependent on patients’ active participation in their own self-care behaviors including prescribed diets.ObjectivesThe purpose of the present study was to investigate the effectiveness of educational intervention based on psychological factors on nutritional behaviors as well as levels of fasting blood sugar (FBS) and glycated hemoglobin (HbA1c) in patients with T2D referring to diabetes clinics and healthcare centers in the city of Izeh, Iran.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 45 publications
(44 reference statements)
2
25
1
Order By: Relevance
“…Eighteen trials were conducted in upper middle-income countries [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], nine in lower middle-income countries [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and two in low-income countries [ 48 , 49 ]. The total sample size was 16,670, with individual study participants ranging from 41 [ 49 ] to 8120 [ 40 ], with 11 of the 30 studies included having a sample size greater than 200.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eighteen trials were conducted in upper middle-income countries [ 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ], nine in lower middle-income countries [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ] and two in low-income countries [ 48 , 49 ]. The total sample size was 16,670, with individual study participants ranging from 41 [ 49 ] to 8120 [ 40 ], with 11 of the 30 studies included having a sample size greater than 200.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 30 included trials, 24 of the interventions were described as diabetes self-management education programs [ 20 , 21 , 22 , 23 , 25 , 26 , 27 , 29 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 48 ], where the focus was on disease management skills including decision making, problem solving, and action planning. These programs were multifactorial in terms of their content.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a randomized controlled trial conducted by Kulzer et al (2009), well-established small group education sessions, that include education on the modifiable risk factors, were more effective in reducing the incidence of T2D when compared to written information. Education programs about T2D self-management were also found to be successful in improving health outcomes and preventing T2D-related complications (Gallé et al, 2017;Salahshouri et al, 2018). Salahshouri et al, found that education sessions on T2D self-management played an important role in changing the perceptions and beliefs of persons with T2D, which may influence their health outcomes.…”
mentioning
confidence: 99%
“…However research conducted in Pacar Keling and Gading of Surabaya City 2015 showed that environmental health interventions did not cause a differences in attitude but only knowledge (23). TB control programs are unable to succeed with extensive service availability only.…”
Section: Introductionmentioning
confidence: 99%